Ring of hate : the Brown Bomber and Hitler's hero, Joe Louis v. Max Schmeling and the bitter propaganda war /: the Brown Bomber and Hitler's hero, Joe Louis v. Max Schmeling and the bitter propaganda war. (2011) - Unknown
No abstract available